Metode Pembelajaran Hafalan Surat-Surat Pendek pada Anak Usia Dini RA Full Day Se-Kabupaten Bantul - Retnowati, Yuni (Al-Athfal: Jurnal Pendidikan Anak, 2019)
This paper is an analysis of learning methods for memorizing short letters in RA Full Day in Bantul Regency, Yogyakarta which includes RA IT Ar-Royyan, RA Ar-Raihan, RA Bunayya ICBB, RA Tahfidz Alqur'an Jamilurrohman, RA Beniso, RA Jogja Citra, RA Permata Hati Al-Mahalli, and RA Masyithoh Tlenggongan. This study aims to find out the right method in learning to memorize short letters in RA Full Day in Baul Regency, Yogyakarta. This type of research methods is used by observation, interview, documentation and triangulation methods. The results obtained in the study show that the method for learning memorization of short letters that is appropriate to apply is the Method of Qira'ati and Iqro. The obstacles faced by the teachers in applying these methods include low memorization ability; lack of parental attention to children's religious activities at home and in the community; children prefer to play rather than participating in memorizing short letters in the Qur'an; and hyperactive child behavior.